2017
DOI: 10.3892/or.2017.5610
|View full text |Cite
|
Sign up to set email alerts
|

Association of long-chain acyl-coenzyme A synthetase 5 expression in human breast cancer by estrogen receptor status and its clinical significance

Abstract: Abstract. The lipid metabolic enzymes are considered candidate therapeutic targets for breast cancer. Long-chain acyl-coenzyme A (CoA) synthase (ACSL) is one of lipid metabolic enzymes and converts free-fatty acid to fatty acid-CoA. Five ACSL isoforms including ACSL1, ACSL3, ACSL4, ACSL5 and ACSL6 are identified in human. High ACSL4 expression has been observed in aggressive breast cancer phenotype. However, the role of other isoforms is still little-known. We therefore, analyzed the expression of ACSL isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…A recent bioinformatics study (37) utilizing online databases Oncomine (https://www.oncomine.org/resource/login .html) and PrognoScan (http://www.abren.net/PrognoScan/) stated certain novel associations between ACSL expression and cancer survival outcomes. On the one hand, which was in line with previous findings (12,18,27), the study showed that the overexpression of either ACSL1 or ACSL4 was associated with a poorer prognosis in patients with colon cancer, and that ACSL5 downregulation was associated with poor survival in breast cancer patients. On the other hand, the study suggested certain novel links.…”
Section: Deregulated Expression Of Acsls In Clinical Cancersupporting
confidence: 91%
See 3 more Smart Citations
“…A recent bioinformatics study (37) utilizing online databases Oncomine (https://www.oncomine.org/resource/login .html) and PrognoScan (http://www.abren.net/PrognoScan/) stated certain novel associations between ACSL expression and cancer survival outcomes. On the one hand, which was in line with previous findings (12,18,27), the study showed that the overexpression of either ACSL1 or ACSL4 was associated with a poorer prognosis in patients with colon cancer, and that ACSL5 downregulation was associated with poor survival in breast cancer patients. On the other hand, the study suggested certain novel links.…”
Section: Deregulated Expression Of Acsls In Clinical Cancersupporting
confidence: 91%
“…By contrast, ACSL5 appears to exhibit the opposite function in cancer. ACSL5 was downregulated in colon (26) and breast (27) cancer, where ACSL1 and ACSL4 were upregulated. ACSL5 was also decreased in bladder cancer (28).…”
Section: Deregulated Expression Of Acsls In Clinical Cancermentioning
confidence: 97%
See 2 more Smart Citations
“…ACSL5 is a member of Acyl-CoA synthetase long-chain family that unlike the other members of ACSL family, provokes β-oxidation [31] or triacylglycerols storage [32] due to its cellular location. ACSL5 dysregulation was previously reported in bladder cancer [33], breast cancer [33,34], glioma [35], glioblastomas [36], and pancreatic ductal adenocarcinoma [37]. Meanwhile, the expression status of ACSL5 in CRC tumors is vague.…”
Section: Plos Onementioning
confidence: 99%